Generation Z's Reception of Bullying Representation in the Korean Drama “Pyramid Game”: An Analysis from Stuart Hall's Perspective - Athok Murtadlo; Anita Agustina Wulandari; Aulia Afniar Rahmawati; Noufal Rangga Saputra (LONTAR: Jurnal Ilmu Komunikasi, 2026)
The increasing popularity of Korean dramas as part of the Korean Wave has positioned them not only as entertainment media but also as a medium for representing various social issues, including bullying. This study aims to analyze Generation Z's reception of the representation of bullying in the Korean drama Pyramid Game using Stuart Hall's Reception Analysis. The research employed a qualitative approach with a reception analysis method involving six Generation Z informants aged 19–29 years who had watched all episodes of Pyramid Game. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model by classifying audience interpretations into dominant-hegemonic, negotiated, and oppositional positions. The findings indicate that Generation Z generally interprets bullying in the “Pyramid Game” as a form of structural violence legitimized through social hierarchy rather than merely interpersonal aggression. Most informants occupied the dominant-hegemonic position by accepting the drama's primary message that bullying reflects systemic injustice. Several informants adopted a negotiated position by considering social risks before resisting bullying, while oppositional interpretations appeared only partially regarding bystander behavior and acts of retaliation. The study concludes that Pyramid Game functions not only as entertainment but also as a medium for social education that encourages critical awareness, empathy, and resistance toward systemic bullying among Generation Z.